Use of Educational Comic Media Assisted by The Think Pair Share (TPS) Learning Model to Improve Literacy in State Elementary School 067248 Medan - Jeni Yolanda (Journal of Elementary School Education, 2026)
This study aims to describe the implementation process and analyze the improvement of literacy skills of fifth-grade students of SD Negeri 067248 Medan through the use of educational comic media assisted by the Think Pair Share (TPS) learning model. The main problem in this study is the low interest in reading and the ability to understand students' texts caused by the dominance of conventional methods. This type of research is Classroom Action Research (CAR) which is carried out in two cycles, including the planning, implementation, observation, and reflection stages. The research subjects consisted of fifth-grade students of SD Negeri 067248 Medan in the 2024/2025 academic year. Data were collected through literacy learning outcome tests (quantitative) and activity observation sheets (qualitative). The results of the study indicate that the integration of visual and communicative educational comic media with TPS syntax (thinking independently, pairing, and sharing) is able to create an interactive learning atmosphere. There was a significant increase in students' literacy skills from the pre-cycle to the second cycle which met the classical success indicator of 75%. The conclusion of this study is that the use of educational comic media assisted by the TPS model is effective in improving literacy skills and student learning activities in elementary schools.